Prevalence of hypertensive disorders of pregnancy and pregnancy outcomes in Sub-Saharan Africa: A systematic review and meta-analysis - Gemechu, Kasiye Shiferaw (Womens Health (Lond), 2020)
Hypertensive disorders of pregnancy are one of the leading causes of poor pregnancy outcomes and are associated with increased rates of maternal mortality, preterm birth, small for gestational age newborns, stillbirth, and neonatal death. The overall and type-specific prevalence of hypertensive disorders of pregnancy and associated pregnancy outcomes are unknown in Sub-Saharan Africa. Therefore, this review aimed to identify the prevalence of hypertensive disorders of pregnancy and associated pregnancy outcomes in Sub-Saharan Africa. A systematic review and meta-analysis were conducted on observational facility-based studies irrespective of publication status, sample size, language, and follow-up duration from 19 countries between the years 2000 and 2018 in Sub-Saharan Africa. A review of studies using PubMed, EMBASE, African Index Medicus, and African Journals Online was completed with independent extraction of studies by review authors using the predefined inclusion criteria. Quality and risk of bias of individual studies were assessed using the Joanna Briggs Institute Checklist. Random effects model was used to estimate the pooled prevalence of hypertensive disorders of pregnancy and type-specific hypertensive disorders of pregnancy. A pooled adjusted odds ratio with 95% confidence interval for each study was calculated using comprehensive meta-analysis version 2 software to estimate the association of hypertensive disorders of pregnancy and its outcomes. The existence of heterogeneity was assessed using I(2) and its corresponding P value. We assessed the presence of publication bias using the Egger’s test. Subgroup analysis was performed to assess the potential effect of variables, and a sensitivity analysis was conducted to assess any undue influence from studies. The analysis included 70 studies. The pooled prevalence of hypertensive disorders of pregnancy (all types combined), chronic hypertension, gestational hypertension, preeclampsia, and eclampsia were 8% (95% confidence interval = [5, 10]), 0.9% (95% confidence interval = [0.4, 1.8]), 4.1% (95% confidence interval = [2.4, 7]), 4.1% (95% confidence interval = [3.2, 5.1]), and 1.5% (95% confidence interval = [1, 2]), respectively. Compared with normotensive pregnant or postpartum women, women with hypertensive disorders of pregnancy were associated with increased risk of maternal mortality, odds ratio = 17 (95% confidence interval = [9.6, 28.8]); cesarean section, odds ratio = 3.1 (95% confidence interval = [1.7, 5.6]); perinatal mortality, odds ratio = 8.2 (95% confidence interval = [2.8, 24]); low birth weight, odds ratio = 3.2 (95% confidence interval = [2, 5]); and preterm delivery, odds ratio = 7.8 (95% confidence interval = [2.5, 25.3]) according to this analysis. The pooled prevalence of hypertensive disorders of pregnancy was high in Sub-Saharan Africa compared to those reported from other regions. Pregnant or postpartum women with hypertensive disorders of pregnancy have increased risk of maternal mortality, cesarean section, preterm delivery, perinatal mortality, and low birth weight newborn. Therefore, creating awareness of the risks of hypertensive disorders of pregnancy is essential. Pregnant women with hypertensive disorders need due attention to manage appropriately and more importantly to have favorable outcomes in this population.